Bioinspired Nanoparticulate Medical Glues for Minimally Invasive Tissue Repair. Issue 16 (27th July 2015) - Lee, Yuhan; Xu, Chenjie; Sebastin, Monisha; Lee, Albert; Holwell, Nathan; Xu, Calvin; Miranda Nieves, David; Mu, Luye; Langer, Robert S.; Lin, Charles; Karp, Jeffrey M.
Abstract : Delivery of tissue glues through small‐bore needles or trocars is critical for sealing holes, affixing medical devices, or attaching tissues together during minimally invasive surgeries. Inspired by the granule‐packaged glue delivery system of sandcastle worms, a nanoparticulate formulation of a viscous hydrophobic light‐activated adhesive based on poly(glycerol sebacate)‐acrylate is developed. Negatively charged alginate is used to stabilize the nanoparticulate surface to significantly reduce its viscosity and to maximize injectability through small‐bore needles. The nanoparticulate glues can be concentrated to ≈30 w/v% dispersions in water that remain localized following injection. With the trigger of a positively charged polymer (e.g., protamine), the nanoparticulate glues can quickly assemble into a viscous glue that exhibits rheological, mechanical, and adhesive properties resembling the native poly(glycerol sebacate)‐acrylate based glues. This platform should be useful to enable the delivery of viscous glues to augment or replace sutures and staples during minimally invasive procedures. Abstract : Methods to deliver viscous medical glues to tissues through small incisions or with small channels are critical for minimally invasive surgeries. Inspired by the granule‐packaged glue delivery system of sandcastle worms, nanoparticulate formulation of viscous hydrophobic light‐activated adhesive based on poly(glycerol sebacate)‐acrylate is shown here.